Occurrence of Selected Persistent Organic Pollutants in Bosnia and Herzegovina: A Systematic Review - Lugušić, Aida; Porobić, Aleksandra; Đeđibegović, Jasmina (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2025)
Persistent organic pollutants (POPs) are compounds that are recognized as significant health and environmental hazards, and their use and emission have been restricted or limited by the Stockholm Convention. Despite the control measures foreseen by the international treaties, the presence in the environment is still evident. Bosnia and Herzegovina is a party to the Stockholm Convention, but regular integrative monitoring of POPs occurrence in the environment has not been established. Data on POPs concentrations reported by various research groups and institutions are scattered in the available publications, making a general assessment difficult. This paper aims to summarize data on the presence and levels of selected POPs in environmental and biological samples from Bosnia and Herzegovina, which can aid in planning further monitoring actions, the assessment of effects of already implemented control measures, and policy decision making. The main findings indicate the presence of organochlorine pesticides (OCPs), polychlorinated biphenyls (PCBs), and polycyclic aromatic hydrocarbons (PAHs) in most of the matrices (soil, air, water, sediment, and certain food). Potential ecological or health risks cannot be excluded in respect to heptachlor (Bosna river basin), dichlorodiphenyltrichloroethane (in free-range hen eggs), PCBs (in free-range hen eggs and in Modrac Lake sediment), and PAHs (in agricultural soil in Spreča valley and in sediments from Bosna and Spreča rivers).